Periampullary Variceal Bleeding: An Atypical Complication of Portal Hypertension. (3rd May 2018) - Farkas, Zahava C.; Chugh, Priyanka; Frager, Shalom; Haq, Khwaja F.; Khan, Muhammad Ali; Solanki, Shantanu; Esses, Edward; Veillette, Gregory; Bodin, Roxana
Abstract : Variceal bleeding remains a fatal complication of portal hypertension. Periampullary varices are rare and, due to their location, are difficult to diagnose and treat. Similar to esophagogastric varices, they are the result of high portosystemic pressures secondary to intrahepatic causes such as cirrhosis and extrahepatic causes such as portal or splenic vein thrombosis. We report a case of a periampullary varix resulting in hemobilia during endoscopic retrograde cholangiopancreatography (ERCP).